Strategi Media Relations Humas Pemerintah Kabupaten Grobogan Dalam Melaksanakan Publisitas (Studi Deskriptif Kualitatif Tentang Strategi Media Relations Dalam Melaksanakan Publisitas Di Bagian Humas Dan Protokol Sekretariat Daerah Kabupaten Grobogan) - Aditrianto, Ridho, Drs. Joko Sutarso, S.E, M.Si (2017)
A government public relation has significant role in opening opportunities to the public to access certain information. Information that will be share to public should be accurate, understandable, and fast in order to synchronyze government's policies to the need of society. this has been carried out by the public relation department of the district government of Grobogan which plays its role as source of information to the public and media. The district government of Grobogan has involved its public relation in spreading information through mass media. this research belonged to qualitative descriptive research which describes media relations done by the public relation department of the district government of Grobogan in managing which will be published to attract publicity. Source of data taken was interview with the interviewee. The technique of data collection used observation, interview and documentation. Data analysis in this research applied data collecting, data reduction, presentation, dan conclusion or verification. This research concluded that media relations strategy taken by the public relation department of the district government of Grobogan included three roles. Those three roles were the roles as public relation, as media relations, and as information publicity. The public relation department thought that publicity was important for the reason of the ability to build good relationship with the mass media in Grobogan regency. Communication taken by the public relation department to the media aimed to increase the understanding to the society.